Application of interspecific Somatic Cell Nuclear Transfer (iSCNT) in sturgeons and an unexpectedly produced gynogenetic sterlet with homozygous quadruple haploid - Fatira, Effrosyni; Havelka, Miloš; Labbé, Catherine; Depincé, Alexandra; Iegorova, Viktoriia; Pšenička, Martin; Saito, Taiju (Scientific reports, 2018)
Somatic cell nuclear transfer (SCNT) is a very promising cloning technique for reconstruction of endangered animals. The aim of the present research is to implement the interspecific SCNT (iSCNT) technique to sturgeon; one fish family bearing some of the most critically endangered species. We transplanted single cells enzymatically isolated from a dissociated fin-fragment of the Russian sturgeon (Acipenser gueldenstaedtii) into non-enucleated eggs of the sterlet (Acipenser ruthenus), two species bearing different ploidy (4n and 2n, respectively). Up to 6.7% of the transplanted eggs underwent early development, and one feeding larva (0.5%) was successfully produced. Interestingly, although this transplant displayed tetraploidism (4n) as the donor species, the microsatellite and species-specific analysis showed recipient-exclusive homozygosis without any donor markers. Namely, with regards to this viable larva, host genome duplication occurred twice to form tetraploidism during its early development, probably due to iSCNT manipulation. The importance of this first attempt is to apply iSCNT in sturgeon species, establishing the crucial first steps by adjusting the cloning-methodology in sturgeon's biology. Future improvements in sturgeon's cloning are necessary for providing with great hope in sturgeon's reproduction.
Keywords: Russia; druhová specificita; Male; homozygot; Genotype; Nuclear Transfer Techniques; mikrosatelitní repetice; Cloning, Organism; Endangered Species; techniky jaderného přenosu; Haploidy; klonování organismů; mužské pohlaví; Homozygote; Species Specificity; ryby; haploidie; Fishes; Microsatellite Repeats; Animals; ženské pohlaví; zvířata; Rusko; tetraploidie; genotyp; Tetraploidy; Female; ohrožené druhy